Robust control of cascaded uncertain nonlinear systems - Su, Weizhou. (2009)
This thesis will discuss robust stabilization and robust performance for some classes of nonlinear systems. First, we consider a class of minimum phase nonlinear systems which are subjected to bounded parameter uncertainties. The problem addressed is to design a static state feedback controller such that the resulting closed loop system is passive for all admissible uncertainties. A nonhnear passifying controller is derived. It is shown that the controller also guarantees the system to be zero input bounded-state stable.